The Relationship of The Sultanate of Dar Ouaddaï with The Ottoman Empire - Adam, Assadik Ahmad (Arab Journal for Sciences and Research Publishing, 2022)
The aim of this study is to clarify the extent of the relationship that prevailed between the Sultanate of Ouaddaï and the Ottoman Sultanate, as well as to identify the extent of the political and cultural relationship that was between them. The problem with this topic lies in the fact that it is one of the thorny issues that needs to be studied and scrutinized to clarify what was prevalent between the two sultanates, and to remedy that it needs many sources and references, but most of what was found from these sources and references dealt with the subject in indirect ways, except for the rare ones. Research method, followed in this study, the historical method, and the descriptive method. Among the most important results: The Wadayi Sultanate was one of the sultans that was able to extend its influence and rule over large and prestigious parts. This extended to the Libyan borders in the north, to the country of Jankhar in the south, to Darfur in the east, and to the kingdom of Kanem and Bagrami in the northwest and west. Most of the relations that prevailed between the Sultanate of Wadi and the Ottoman Sultanate were indirect relations.